CHALLENGES AND OPPORTUNITIES FOR ISLAMIC EDUCATION IN THE 5.0 ERA IN OGAN KOMERING ULU REGENCY - Aripin, Azwar; Cahyono, Aris Eko; Sepriyadi , Heri; Rustandi, Jajang (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to analyze the challenges and opportunities of Islamic education in the 5.0 era, particularly in Ogan Komering Ulu (OKU) Regency, as part of an effort to understand the readiness of Islamic educational institutions in facing digital transformation and the demands of the 21st century. The background of this study is based on the urgent need for an Islamic education system that can adapt to technological developments without neglecting spiritual values and Islamic character. This study uses a qualitative approach with an exploratory descriptive design. The research subjects consisted of madrasah principals, Islamic education teachers, pesantren administrators, students, and representatives from the OKU District Education Office and the Ministry of Religious Affairs. Data was collected through in-depth interviews, participatory observation, and documentation, then analyzed using thematic analysis techniques. The results of the study indicate that the main challenges of Islamic education in OKU lie in the limitations of technological infrastructure, the low competence of teachers in utilizing digital technology, and the absence of strategic planning for digital transformation in education. Meanwhile, opportunities that can be developed include the high enthusiasm of students for digital learning, the potential for collaboration with local communities, and strong social and cultural support for Islamic education. Islamic education in OKU is in a strategic position to undertake sustainable transformation, provided that there is contextual policy support, structured teacher training, and the integration of Islamic values in the use of technology. These findings are expected to serve as a foundation for the development of inclusive, adaptive, and competitive Islamic education in the 5.0 era.